Introduction to Canon Law - Coriden, James A. (Continuum International Publishing Group, 2004)
Catholic canon law changes very slowly, but it constantly adds rules, interpretations, and applications. Some canons are frequently invoked, and others rarely used, quietly pass from memory. In the dozen or so years since this introduction to canon law was first written, there have been many changes and adaptations. This is one reason for a revised edition, although many of the alterations are too subtle to be captured in an introductory treatment.A second reason is to include some of the many new resources, commentaries, and explanations which authorities in the field have made available.Sinc.